Pengaruh Pengangguran, Pertumbuhan Ekonomi dan Upah Minimum Terhadap Tingkat Kemiskinan di Kabupaten Aceh Barat Daya - Veronica, Putri Bahri; Alisman, Alisman; Risma, Okta Rabiana; Arisna, Puput; Sani, Sri Rosmiati (Universitas Pahlawan Tuanku Tambusai, 2024)
We want to examine poverty in our research. Using data collected from BPS Aceh Barat Daya between 2005 and 2024, we can see that poverty is the dependent variable while unemployment, economic growth, and minimum wage are the independent variables. Using multiple linear regression as its methodology, this research found that minimum wage increases and economic growth both somewhat affect poverty levels, while unemployment had no such influence. All three independent variables unemployment, economic growth, and minimum wage—have a substantial impact on poverty; the R-Square value of 94% indicates that these three factors explain 94% of the variation in poverty, while the remaining 6% are attributable to factors outside the scope of this research. Keyword: Poverty, Unemployment, Economic Growth, Minimum Wage.